HTML comprehensive concepts and techniques - Shelly, Gary B; Woods, Denise M.; Dorin, William J. (Shelly Cashman series, 2009)
Part of the highly successful Shelly Cashman series, this text provides a comprehensive introduction to HTML and leads the user through a clear, step-by-step, screen-by-screen approach to learning. Readers learn how to create a Web page using HTML, format the page, add graphics, and more.